2007
DOI: 10.1103/physrevlett.98.163001
|View full text |Cite
|
Sign up to set email alerts
|

Above Threshold Dissociation of Vibrationally ColdHD+Molecules

Abstract: The experimental study of molecular dissociation of H2+ by intense laser pulses is complicated by the fact that the ions are initially produced in a wide range of vibrational states, each of which responds differently to the laser field. An electrostatic storage device has been used to radiatively cool HD+ ions enabling the observation of above threshold dissociation from the ground vibrational state by 40 fs laser pulses at 800 nm. At the highest intensities used, dissociation through the absorption of at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 25 publications
3
51
1
Order By: Relevance
“…The ion trap has been briefly reported in an earlier publication (Orr et al 2007) but a more in-depth description is provided here. The instrument operates in a manner analogous to a laser cavity (Pedersen et al 2002, Ota et al 2006, with electrostatic potentials and a linear geometry which preserves the keV beam characteristics of the injected ions.…”
Section: Ion Trapmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion trap has been briefly reported in an earlier publication (Orr et al 2007) but a more in-depth description is provided here. The instrument operates in a manner analogous to a laser cavity (Pedersen et al 2002, Ota et al 2006, with electrostatic potentials and a linear geometry which preserves the keV beam characteristics of the injected ions.…”
Section: Ion Trapmentioning
confidence: 99%
“…We use HD + rather than H + 2 or D + 2 as it has a permanent dipole moment and will radiatively cool into its ground vibrational state after approximately 300 ms. As the ions are moving in the trap with keV energies, we are also able to study the pure dissociation of the molecular ion through emission of neutral particles, without the interference of any charged fragments produced from the ionization process. A brief report of this method has been previously communicated (Orr et al 2007), in which the above threshold dissociation of HD + (υ = 0) was found to be the dominant dissociation process. This had not previously been observed experimentally as the ground state dissociation was overwhelmed by signal from excited states.…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing rapid developments in intense femtosecond (fs) and attosecond (as) laser technologies and some new theoretical and computational approaches in full dimensionality, this simplest molecule, as well as its isotopes HD + and D + 2 , have served as a prime testing ground in recent years to explore fundamental processes such as the electron localization in dissociation channels [4,5], the double-slit interference effect [6][7][8], the mapping of vibrational wave packets followed by Coulomb explosion [9], and above-threshold dissociation [10,11] for laser wavelengths ranging from x-ray to infrared.…”
mentioning
confidence: 99%
“…The pre-trapping of the ions is combined with a fast pulsing of the beam, both by emptying the trap contents by repeated pulses synchronized with a FLASH pulse train and by pulsing of a directly transported continuous ion beam. In principle, ion trapping directly in the interaction region, as demonstrated for laser multiphoton dissociation of fast molecular ions [29], offers more flexibility and efficiency; however, this technique somewhat compromises the fragment imaging and hence was not implemented in the initial experiments. In test operation, small electrostatic ion traps around the photon crossing have been shown to be operational.…”
Section: Apparatusmentioning
confidence: 99%